Potential Spread of Parasites Through Fly - Marthin Sufandi Banamtuan; Oktofianus Sila; Debora Gaudensiana Suluh; Ragu Theodolfi; Sucipto , Mega Rahmawati (Poltekkes Kemenkes Kupang, 2024)
Parasites that can be transmitted by flies include Ascaris lumbricoides, Trichuris trichiura, and hookworm eggs. The purpose of this study was to determine the potential for parasite spread through flies in food stalls at the Naikoten 1 Inpres Market, Kupang City. This type of research is descriptive research. The research variables are fly density levels, fly types, and parasites on fly bodies. The sample in this study was 4 food stalls that have the potential for parasite transmission at the Naikoten 1 Inpres Market, Kupang City. Data collection methods were obtained by measuring fly density levels using a Flygrill, as well as examining fly types and parasites on fly bodies using a microscope. The results of the fly density measurement study at food stalls at the Naikoten 1 Inpres Market, Kupang City were categorized as low (100%). The types of flies caught were 95% Musca domestica (house flies) and 5% Sarcophaga flies. The results of the worm egg examination found 35% Ascaris lumbricoides and 5% Trichuris Trichiura. For this reason, there needs to be socialization and community empowerment in food and drink sanitation so that the chain of transmission of worm eggs to humans can be broken through fly control and attention to the cleanliness of sales locations.